2021
DOI: 10.3390/coatings11111380
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a UV Photodetector Based on n-TiO2/p-CuMnO2 Heterostructures

Abstract: The heterojunction based on n-TiO2 nanolayer/p-CuMnO2 thin film was achieved using an efficient two-step synthesis process for the fabrication of a UV photodetector. The first step consisted of obtaining the TiO2 nanolayer, which was grown on titan foil by thermal oxidation (Ti-TiO2). The second step consisted of CuMnO2 thin film deposition onto the surface of Ti-TiO2 using the Doctor Blade method. Techniques such as X-ray diffraction, UV-VIS analysis, SEM, and AFM morphologies were used for the investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…Researchers in the recent times have shown various configurations of p-n junction based on thin film (TF), core-shell etc, for high performance PDs application [5]. Mircea Nicolaescu et al reported n-TiO 2 /p-CuMnO 2 TF based HS PD where separation of charge carries was ensued at good amount [6]. Yachao Wang et al reported all-oxide NiO/β-Ga 2 O 3 p-n TF HS based PD for good stability and reproducibility of its optoelectronic characteristics [7].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in the recent times have shown various configurations of p-n junction based on thin film (TF), core-shell etc, for high performance PDs application [5]. Mircea Nicolaescu et al reported n-TiO 2 /p-CuMnO 2 TF based HS PD where separation of charge carries was ensued at good amount [6]. Yachao Wang et al reported all-oxide NiO/β-Ga 2 O 3 p-n TF HS based PD for good stability and reproducibility of its optoelectronic characteristics [7].…”
Section: Introductionmentioning
confidence: 99%
“…The doping of metal elements can increase the carrier concentration and the semiconductor properties of SnO 2 , and at the same time change the surface morphology of the electrode and the grain size of the active layer, thereby affecting the electrocatalytic activity of the electrode. [ 143 ] Mn was doped into the SnO 2 –Sb anode layer, and it was found that the Mn‐doped electrode exhibited better electrochemical performance than the undoped Ti/SnO 2 –Sb electrode. [ 42 ] The decolorization rate of MB dye wastewater reached 97% within 10 min at a low cell voltage of 4.5 V, which is 29% higher than that of the undoped electrode.…”
Section: Ti/sno2 Electrodementioning
confidence: 99%
“…Ultraviolet (UV) photodetectors have found widespread applications across diverse domains, including chemical analysis, water purification, flame detection, early missile plume identification, secure space-to-space communication, chemical and biological sensing, and environmental monitoring. , Ozone-layer depletion can cause the harmful UV radiation to penetrate our atmosphere and reach the Earth’s surface . However, the hazardous effects of UV-A to UV-C radiation on human health, such as premature aging, skin damage, and the risk of cancer, underscore the importance of accurately detecting and avoiding these harmful rays. …”
Section: Introductionmentioning
confidence: 99%